Communication, Information and Education (CIE) using Five Finger Labels to Reduce Anxiety of the Patient’s Family - Ariyanti, Fitria Wahyu; Fatmawati, Atikah; Haryadi, Tri (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
During the treatment process, anxiety could've been felt by the family that had their member treated in the hospital. This research is purposed for knowing the effect of Communication, Information, and Education (CIE) using  five-finger labels on the level of anxiety of the patient's family in the emergency department. This research used quasi-experimental with pre-post test with a control group design. The sample in the research is the patient's family which is in the yellow zone of the emergency department counted 60 respondents, selected with purposive sampling. Instruments that were selected are the Anxiety questionnaire State Anxiety Inventory (S-AI) form Y. The results showed that in the experimental group, there was an increase in the number of mild anxiety levels from 53.3% to 80%, a decrease in the number of moderate anxiety levels from 43.3% to 20%, a decrease in the level of severe anxiety from 3.3% to 0%. In the control group, there was an increase in the number of mild anxiety levels from 53.3% to 60% and a decrease in moderate anxiety levels from 46.7% to 40%. The results of the Mann-Whitney statistical test obtained a significance value (p) of 0.010, which means that there was an effect of CIE using five-finger labels on the anxiety level of the patient's family in the emergency room. The results of this study are expected to be applied as an intervention in reducing the anxiety of the patient's family in the emergency room.